Umpasa dan Nilai Budaya Mangalahat Horbo: Kajian Antropolinguistik - Basaria, Ida; Hutabarat, Gaby Gabriela; Habeahan, Marta Erinda; Sembiring, Gressella Sesinta (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
This article examines umpasa as the determinant of the validity of the Mangalahat Horbo ritual and as a vehicle for transmitting the cultural values of the Batak Toba people from an anthropolinguistic perspective. Mangalahat Horbo is a buffalo sacrifice ritual that functions simultaneously as a cosmological, political, and linguistic event. This study employs a descriptive qualitative approach using three theoretical frameworks: Dell Hymes' (1974) SPEAKING model to analyze the ritual as a speech event, Roland Barthes' (1968) semiotics to dissect the denotative and connotative meanings of umpasa, and Kluckhohn's (1953) theory of cultural values and Sibarani's (2014) local wisdom theory to identify embedded cultural values. The findings reveal that umpasa operates on three simultaneous layers of meaning: pragmatic-performative, social-hierarchical, and cosmological-ecological. Umpasa is not merely an aesthetic ornament but a constitutive element of the ritual that shapes the social and cosmological reality of the Bius community. Eight cultural values are identified: communicative courtesy, adat knowledge transmission, self-restraint, collective responsibility, cultural preservation, cosmological reciprocity, distributive justice, and ecological harmony. This study affirms the urgency of anthropolinguistic documentation of Mangalahat Horbo before the Parhata masters of umpasa diminish further.